Penegakan Hukum terhadap Perlindungan Terumbu Karang di Kabupaten Raja Ampat - Arya, Surandi Woong; Markus, Dwi Pratiwi; Ali , Muhammad (Universitas Muhammadiyah Surabaya, 2024)
Massive exploitation of coral reefs and their surrounding ecosystems often occurs without considering conservation and sustainability, especially in tourist destinations, as seen in Raja Ampat Regency. The research employed both normative juridical and empirical juridical approaches with a descriptive-analytical approach. The types of data used were primary data, obtained directly from respondents, and secondary data, obtained from literature studies, documentation, and interviews. The research findings indicate that the legal norms governing law enforcement for coral reef protection in Raja Ampat Regency constitute violations of norms with strict sanctions, providing education to combat theft and/or destruction of marine ecosystems, with the aim of raising awareness among the public that such actions are criminal offenses. The enforcement of sanctions for legal violations against coral reefs in Raja Ampat Regency takes the form of patrols to monitor criminal acts of ecosystem destruction and also conducts socialization to help the community understand the consequences of damaging marine ecosystems. The concept presented by the author in the research reaffirms the importance of the role of parents and all elements of society in maintaining public order and security, particularly community development. It emphasizes that it is not solely the responsibility of the police, as without the functioning and involvement of parents and community elements, the police cannot effectively and efficiently carry out their duties in fostering the community.